GEOPHYSICAL SURVEY RESULTS AT THE ANCIENT BURIALS OF THE UGUUMUR SITE (DORNOD AIMAG, KHULUNBUIR SUM) - N.ARVISBAATAR; G.BATSUKH; S.LANTUU; TS.BAATARCHULUUN (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2023)
Underground structure of ancient burials in Takhilgat and Tsuvraa mountains, Khulunbuir sum, Dornod aimag were investigated by geophysical method of magnetometry. The results of the study show that magnetic anomalies caused by different geological formations (mineral structure, rifts and etc.) may demonstrate about the existence of a stone construction under ground at the site of investigation and that geophysical methods can be effective for archaeological investigations of the burials and other underground structures.